2016
DOI: 10.1007/s00204-016-1868-7
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic metabolism in differentiated human bronchial epithelial cells

Abstract: Differentiated human bronchial epithelial cells in air liquid interface cultures (ALI-PBEC) represent a promising alternative for inhalation studies with rodents as these 3D airway epithelial tissue cultures recapitulate the human airway in multiple aspects, including morphology, cell type composition, gene expression and xenobiotic metabolism. We performed a detailed longitudinal gene expression analysis during the differentiation of submerged primary human bronchial epithelial cells into ALI-PBEC to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…We recently showed that the ALI-differentiated cultures used in our laboratory for exposures to e.g. diesel exhaust (Zarcone et al, 2016;Zarcone et al, 2017) or cigarette smoke (Amatngalim et al, 2015;Amatngalim et al, 2017) show higher expression of various genes involved in biotransformation compared to undifferentiated cultures (Boei et al, 2016). Furthermore, we showed that undifferentiated cultures, in contrast to differentiated cultures, are incapable of metabolic conversion of a variety of different p450 substrates.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…We recently showed that the ALI-differentiated cultures used in our laboratory for exposures to e.g. diesel exhaust (Zarcone et al, 2016;Zarcone et al, 2017) or cigarette smoke (Amatngalim et al, 2015;Amatngalim et al, 2017) show higher expression of various genes involved in biotransformation compared to undifferentiated cultures (Boei et al, 2016). Furthermore, we showed that undifferentiated cultures, in contrast to differentiated cultures, are incapable of metabolic conversion of a variety of different p450 substrates.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 83%
“…Expression of CYP isoenzymes may be modulated in disease and is affected by e.g. epithelial differentiation (Boei et al, 2016), which may help to explain the differential susceptibility of patients with lung diseases and healthy subjects to inhaled irritants and toxicants. Therefore, cellular differentiation and disease state should be taken into account when developing a model.…”
Section: Requirements For Cell Culture Models For In Vitro Inhalationmentioning
confidence: 99%
“…Previous studies on diseased tortoises found that nasal discharge reduced the sense of smell and hence the ability to locate food (Germano, Zerr, Esque, Nussear, & Lamberski, ). It is also plausible that levels of transcription were also modulated by environmental or behavioral factors that were not addressed in this study (Boei et al, ). We did not quantify the activity levels, internal body temperatures, or metabolic rates for individual tortoises, but realize that temperature changes can have profound effects on metabolism and immunity by modulating important triggers and regulators of immune pathways (Ferguson, Kortet, & Sinclair, ; Sandmeier, Weitzman, & Tracy, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, RNA interference (RNAi), morpholinos, chemical inhibitors and hypomorphic mutations often lead to partial suppression of gene function, whereas null mutations can ablate gene function (Housden et al, 2017). We also know that a host of other factors such as age (Zhang, Drake, Morrison, Oberley, & Kregel, 2002), metabolism (Boei et al, 2017), prior exposure (Louis, Bhagooli, Kenkel, Baker, & Dyall, 2017), and environmental condition (Mangino, Roederer, Beddall, Nestle, & Spector, 2017) can influence these processes. Although pinpointing the specific mechanisms that may control transcription activity in our diseased tortoises is beyond the scope of this paper, our findings provide an opportunity to further explore this phenomenon and highlight the counterintuitive physiological responses often observed in tortoises and other reptiles during disturbance events (authors unpublished work; Sandmeier et al, 2016;Theodorakis et al, 2017).…”
Section: Molecular Roles In Immunitymentioning
confidence: 99%
“…Xenobiotic-metabolizing cytochrome P450 enzymes expressed in bronchial and bronchiolar epithelium, club cells, type II alveolar cells, and alveolar macrophages in human lung activate environmental chemicals, modifying cell biochemical microenvironment and contributing to pathologies such as cancer and COPD [86]. Expression and activity of such enzymes is in part determined by epithelial differentiation, indicating the need for appropriate cellular differentiation in models [87]. Organs-on-Chips offer the possibility to accurately control the regional and temporal biochemical microenvironment of cells through controlled perfusion of growth medium and gases.…”
Section: Biochemical Microenvironmentmentioning
confidence: 99%